2010
DOI: 10.1016/j.pec.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Patient–provider communication and reproductive health among HIV-positive women in Rio de Janeiro, Brazil

Abstract: Adequate provider training to address reproductive health-related issues in a comprehensive, culturally sensitive manner and improved integration of HIV and reproductive health care are urgently needed in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…4,5 While reported communication with HIV providers was not directly measured by Paiva and colleagues, they reported most participants did not feel health professionals were supportive enough or even impartial about their desire to have a child, and that men's knowledge of perinatal transmission risk was low. 4,5 Comparing our data to those of other studies directly assessing communication about future reproductive plans among HIV + men, we found 12 These findings were consistent with an observational study among HIV providers in Rio de Janeiro reporting limited communication about safer sexual practices. 23 While often neglected and far from being routine, sexual and reproductive health is more likely considered for HIV + female patients of reproductive age compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4,5 While reported communication with HIV providers was not directly measured by Paiva and colleagues, they reported most participants did not feel health professionals were supportive enough or even impartial about their desire to have a child, and that men's knowledge of perinatal transmission risk was low. 4,5 Comparing our data to those of other studies directly assessing communication about future reproductive plans among HIV + men, we found 12 These findings were consistent with an observational study among HIV providers in Rio de Janeiro reporting limited communication about safer sexual practices. 23 While often neglected and far from being routine, sexual and reproductive health is more likely considered for HIV + female patients of reproductive age compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6] Recognizing the importance of having children among HIV + men, patients need to be able to discuss and plan such childbearing decision making with their HIV provider and partner. There is growing awareness of the unmet need for reproductive counseling among HIV + women in clinical care, as illustrated by recent studies in Brazil, 12,13 the United States, [14][15][16][17] and sub-Saharan Africa. 18,19 This same need for reproductive counseling among HIV + male patients has been largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Hollen et al [48] concluded that the LCSS demonstrates (1) good feasibility, reliability and content validity and (2) high interrater reliability. Overall, the LCSS has consistently demonstrated good feasibility, reliability (internal consistency) and convergent validity [48,49,50,51]. For this study, Cronbach's α for the total scale was 0.94.…”
Section: Methodsmentioning
confidence: 76%
“…Stigma contributes to communication difficulties (i.e., stereotyping, status and power differentials between majority and minority groups and lack of cultural awareness of health professionals), which are implicated in poorer health service delivery and worse patient outcomes [49]. This barrier exists for many health conditions, including HIV, obesity and mental illness, and results in increased patient distress and poor patient outcomes [22,50,51,58]. Across all stages of disease, patients with lung cancer report inadequate patient communication related to the felt experience of stigma on key topics such as prognosis, palliative care and symptom management [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent qualitative findings from 70 HIV-infected women in Rio de Janeiro (in press) found that with a few positive exceptions, most providers did not communicate at all with their patients about sexual behavior, fertility intentions, or contraception. When providers did make the effort, their form of communication was often closed-ended and perfunctory [35].…”
Section: Introductionmentioning
confidence: 99%